Improvisation of blues rock with electro-fretted violin - Kesendere, Yiğitcan (Genç Bilge Yayıncılık, 2024)
This research has been prepared as a performance article and a research article. Blues music and Blues guitarist and composer B.B. King, who has an unforgettable place in the history of music, performed improvisation with electro and draped violin. During the performance, the infrastructure of the "Chusss Music" Youtube channel titled "E Minor Blues Guitar Backing Track BB King Style" was used. 12 gauge blues chord patterns were used. With the improvisation performance of blues rock with Kesendere, electro pitch violin, He was awarded the "Western Music-String Instruments" award by the International Rast Music Congress and Music Awards. It is very difficult to find orchestras and groups for music performed in groups such as rock music, jazz music and pop music in some cases and regions. Unfortunately, the economic costs of the established orchestras make it difficult for these orchestras to have a long life. It is recommended to use computer-accompanied music infrastructure in the face of such difficulties.
Keywords: Music Education; Müzik Eğitimi Music Performance; Müzik Performansı Music Technology and Recording; Müzik Teknolojisi ve Kayıt